SELEKSI KINERJA SAHAM TERCATAT DI BURSA EFEK JAKARTA MENGGUNAKAN MODEL JENSEN PADA MASA TRANSISI SIKLUS EKONOMI - Mohamad Samsul (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2006)
The purpose of this research is to select the undervalued stock based on the Jensen's model approach. Data used is monthly stock return for 24 months during period of the year 2004 to 2005. Population used is 314 kind of stocks. The result of stock selection shows average undervalued stock of 53 or 17% of stock available for the year 2005. By experiment of 6 kind of initial set, 1 month lead time and 12 time training set, the result shows that the Jensen's model is not enough accurate to estimate the return for the next one month. The average monthly expected return of 13,7% and actual return of 2,9% shows the difference statistically significant. Eventhough, the actual return 2,9% still higher than market return IHSG BEJ of 1,6% on the monthly average. The correlation between the past stock performance and the future stock return is negative and not significant. The difference between return of high past stock performance and low past stock performance is not significant. The correlation between past beta and stock return is not significant. The difference between return of high past beta and low past beta is not significant.